Log Fiesta

Geometry Level 3

Let n n and m m be positive integers where n > m n > m and f ( x ) = log e m x \large f(x) = \log_{e^m}|x| and g ( x ) = log e n x \large g(x) = \log_{e^n}|x| .

(1): If f ( x ) f(x) and g ( x ) g(x) have common tangents at A A and B B and A A' and B B' , find the area of trapezoid A A B B AA'B'B in terms of m m and n n .

(2): If m n m = 1 \dfrac{m}{n -m} = 1 and A A A B B = e 16 A_{AA'B'B} = \dfrac{e}{16} , find m + n m + n .


The answer is 18.

This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try refreshing the page, (b) enabling javascript if it is disabled on your browser and, finally, (c) loading the non-javascript version of this page . We're sorry about the hassle.

1 solution

Rocco Dalto
Dec 17, 2018

x > 0 f ( x ) = log e m ( x ) = ln ( x ) m x > 0 \implies \large f(x) = \log_{e^m}(x) = \dfrac{\ln(x)}{m} and g ( x ) = log e n ( x ) = ln ( x ) n \large g(x) = \log_{e^n}(x) = \dfrac{\ln(x)}{n} \implies f ( a ) = 1 m a = g ( b ) = 1 n b a = n m b f'(a) = \dfrac{1}{ma} = g'(b) = \dfrac{1}{nb} \implies a = \dfrac{n}{m}b \implies

A : ( n m b , ln ( n m b ) ) A:(\dfrac{n}{m}b, \ln(\dfrac{n}{m}b)) and B : ( b , ln ( b ) n ) B:(b, \dfrac{\ln(b)}{n}) \implies

m A B = ln ( ( n m ) n b n m ) b n ( n m ) = 1 b n \large m_{AB} = \dfrac{\ln((\dfrac{n}{m})^n b^{n - m})}{bn(n - m)} = \dfrac{1}{bn} \implies

ln ( ( n m ) n b n m ) = n m ( n m ) n b n m = e n m \large \ln((\dfrac{n}{m})^n b^{n - m}) = n - m \implies (\dfrac{n}{m})^n b^{n - m} = e^{n - m}

b = ( m n ) n n m e a = ( m n ) m n m e \large \implies \large b = (\dfrac{m}{n})^{\frac{n}{n - m}}e \implies a = (\dfrac{m}{n})^{\frac{m}{n - m}} e

\implies

A : ( ( m n ) m n m e , ln ( ( m n ) 1 n m e 1 m ) \large A:((\dfrac{m}{n})^{\frac{m}{n - m}} e, \ln((\dfrac{m}{n})^{\frac{1}{n - m}} e^{\frac{1}{m}})

and,

B : ( ( m n ) n n m e , ln ( ( m n ) 1 n m e 1 n ) \large B:((\dfrac{m}{n})^{\frac{n}{n - m}} e, \ln((\dfrac{m}{n})^{\frac{1}{n - m}} e^{\frac{1}{n}}) .

Using the symmetry about the y y axis we have:

A : ( ( m n ) m n m e , ln ( ( m n ) 1 n m e 1 m ) \large A':(-(\dfrac{m}{n})^{\frac{m}{n - m}} e, \ln((\dfrac{m}{n})^{\frac{1}{n - m}} e^{\frac{1}{m}})

and,

B : ( ( m n ) n n m e , ln ( ( m n ) 1 n m e 1 n ) \large B':(-(\dfrac{m}{n})^{\frac{n}{n - m}} e, \ln((\dfrac{m}{n})^{\frac{1}{n - m}} e^{\frac{1}{n}}) .

and E : ( ( m n ) n n m e , ln ( ( m n ) 1 n m e 1 m ) \large E:((\dfrac{m}{n})^{\frac{n}{n - m}} e, \ln((\frac{m}{n})^{\frac{1}{n - m}} e^{\frac{1}{m}})

A A = 2 ( m n ) m n m , B B = 2 ( m n ) n m n \large AA' = 2(\dfrac{m}{n})^{\frac{m}{n - m}}, \:\ BB' = 2(\dfrac{m}{n})^{\frac{n}{m - n}} and E B = n m n m \large EB = \dfrac{n - m}{nm} \implies

A A A B B = ( m n ) m n m ( n + m n ) ( n m n m ) \large A_{AA'B'B} = (\dfrac{m}{n})^{\frac{m}{n - m}} (\dfrac{n + m}{n})(\dfrac{n - m}{nm}) .

m n m = 1 n = 2 m A A A B B = ( ( 1 2 ) ( 3 2 ) ( 1 2 m ) e = 3 e 8 m = e 16 m = 6 n = 12 m + n = 18 \dfrac{m}{n - m} = 1 \implies n = 2m \implies A_{AA'B'B} = ((\dfrac{1}{2}) (\dfrac{3}{2}) (\dfrac{1}{2m}) e = \dfrac{3e}{8m} = \dfrac{e}{16} \implies m = 6 \implies n = 12 \implies m + n = \boxed{18} .

Incidentally, the slope m A B = g ( b ) = f ( a ) = 1 n ( m n ) n n m e = 1 e ( n m m n ) 1 n m \large m_{AB} = g'(b) = f'(a) = \dfrac{1}{n(\dfrac{m}{n})^{\frac{n}{n - m}} * e} = \dfrac{1}{e}(\dfrac{n^m}{m^n})^{\frac{1}{n - m}} .

0 pending reports

×

Problem Loading...

Note Loading...

Set Loading...